LITERATUR REVIEW: GAMBARAN PEMERIKSAAN KULTUR DARAH DAN POLYMERASE CHAIN REACTION REACTION PADA PASIEN DEMAM TIFOID - Nurmi - Hasbi (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Typhoid fever is a health problem in the world caused by the bacterium Salmonella typhi. The route of transmission of this disease is through oral-faeces. According to WHO it is estimated that every year around the world there are 10 to 21 million cases of typhoid fever. whereas in Indonesia in 2010-2019, the incidence rate is estimated to be around 500 per 100,000 population each year. The inability to make an early laboratory diagnosis often leads to increased morbidity and mortality in cases of typhoid fever. The S. typhi culture examination technique is the gold standard method for confirming the diagnosis of typhoid fever. Polymerase Chain Reacton (PCR) is an in vitro DNA synthesis and amplification technique. PCR technique can be used to amplify DNA segments of pathogenic bacteria millions of times in just a few hours. This study aims to determine the effectiveness of fever examination between culture and PCR techniques. This study used the literature review method which was carried out by collecting library data based on keywords, namely typhoid fever, culture, and PCR. Searching for articles through the Google Scholar and Pubmed databases. The results of the analysis of the literature review with a sensitivity statistical test were 0.001 (p<0.05) and the speficity test was 0.095 (p>0.05). There is a significant difference in terms of sensitivity and no significant difference in terms of specificity of blood culture and polymerase chain reaction (PCR) results